BANK SYARIAH INDONESIA'S STRATEGY IN ATTRACTING THE PUBLIC TO PAYING ZAKAT (CASE STUDY OF BANK SYARIAH INDONESIA GUNUNG TUA BRANCH) - lili anggraini; azwar hamid; sulaiman efendi (Journal Of Sharia Banking, 2022)
The background of this research is tha Islamic banking is an institution that carries out three main functions, namely accepting deposits, lending money, and services. And Islamic Bank Indonesia Gunung Tua has made it easy for customers to pay zakat, because zakat is legally obligatory for every Muslim who has assets. Objects according to the provisions stipulated by Islamc Bank in attaracting the publicto pay zakat (case study of the Indonesia Islamic Bank branch of Gunung Tua). The purpose of this research is to find out the strategy of  Bank Syariah Indonesia branch Gunung Tua old).             The theories that support this research consist of the notion of strategy, Islamic banking, Islamic banking principles, Islamic banking functions, Islamic banking as zakat management, zakat, zakat assets, zakat function, basic zakat obligations, zakat.             This research is a qualitative research with a descriptive approach. The subjects of this research are employees and staff at Bank Syariah Indonesia Gunung Tua thchnical data collection using technical analysis of data using descriptive qualitative.Based on the results of research that has been carried out by researchehers in attracting the public to pay zakat at bank syariah Indonesia gunung tua by explaining what are the advantages that exist at bank syariah Indonesia gunung tua, and providing services for customers for transactions in paying zakat. The strategy carried out by bank syariah Indonesia in attracting the public to pay zakat is to use a marketing mix strategy, namely product, promotion, people, plce.